1982
DOI: 10.1071/ar9820917
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the duration of phases in the pre-anthesis life cycle of spring barley

Abstract: Ear development and ear growth were studied in the progeny of two crosses between a six-row and two two-row spring barley varieties. There were no differences in the rates of primordium initiation amongst the progenies and parents. Duration of ear initiation and ear growth varied amongst the genotypes, and there was a strong negative correlation between the duration of these phases. Duration of ear initiation was correlated with number of leaves, as was the length of life cycle from sowing to anthesis. Surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
4

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 0 publications
7
32
4
Order By: Relevance
“…By contrast, we showed that the number of floret primordia that were initiated before the beginning of stem elongation (W3.5) corresponded to the final number of seeds per spike ( Figure 1B; Supplemental Figure 1B). Therefore, these findings support the idea that the early reproductive phase is critical for yield, as this phase determines the maximum number of floret primordia that may develop into seeds (Appleyard et al, 1982;Kitchen and Rasmusson, 1983). Accordingly, a shortening of the early reproductive phase in S42-IL107 with a dominant Ppd-H1 allele reduced the number of floret primordia compared with Scarlett.…”
Section: The Induction Of the Photoperiod Pathway In The Leaves And Msupporting
confidence: 71%
See 1 more Smart Citation
“…By contrast, we showed that the number of floret primordia that were initiated before the beginning of stem elongation (W3.5) corresponded to the final number of seeds per spike ( Figure 1B; Supplemental Figure 1B). Therefore, these findings support the idea that the early reproductive phase is critical for yield, as this phase determines the maximum number of floret primordia that may develop into seeds (Appleyard et al, 1982;Kitchen and Rasmusson, 1983). Accordingly, a shortening of the early reproductive phase in S42-IL107 with a dominant Ppd-H1 allele reduced the number of floret primordia compared with Scarlett.…”
Section: The Induction Of the Photoperiod Pathway In The Leaves And Msupporting
confidence: 71%
“…A better understanding of the developmental processes that determine potential seed number could enhance the efficiency of breeding programs aimed at improving grain yield. Reproductive development in temperate cereals is divided into three phases based on morphological changes of the shoot apex: leaf initiation (vegetative phase), floret initiation (early reproductive phase), and spike growth (late reproductive phase) (Appleyard et al, 1982;Slafer and Rawson, 1994;González et al, 2002). Waddington et al (1983) developed a quantitative scale for barley and wheat (Triticum aestivum) development based on the morphogenesis of the shoot apex and carpels.…”
Section: Introductionmentioning
confidence: 99%
“…In barley, the pre-anthesis developmental phases include the vegetative phase (leaf initiation), the early reproductive phase (spikelet or floret initiation; from the double ridge to AP) and the late reproductive phase (spike growth and development; from AP to anthesis) (Appleyard et al 1982;Kirby and Appleyard 1987;Slafer and Rawson 1994;Sreenivasulu and Schnurbusch 2012). Variation in the duration of the pre-anthesis developmental phases and morphological changes, particularly during the late reproductive phase, have been reported (Appleyard et al 1982;Kitchen and Rasmusson 1983;Kernich et al 1995b;Kernich et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have postulated that the differences in spikelet mortality between two-and six-rowed barley arise as a result of competition for assimilates (Kirby 1988;Arisnabarreta and Miralles 2004), competition between spikelets per spike (Appleyard et al 1982) or the position of spikelets within the spike (Arisnabarreta and Miralles 2006). Spikelet abortion is generally higher in six-rowed barleys (Frank et al 1992;Kernich et al 1997;Arisnabarreta and Miralles 2004;Arisnabarreta and Miralles 2006) because they possess more fertile spikelet primordia per spike (Whingwiri and Stern 1982;Kirby and Appleyard 1987;Kernich et al 1997;Miralles et al 2000;del Moral et al 2002;Arisnabarreta and Miralles 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation